Obesity phenotype in relation to gene polymorphism among samples of Egyptian children and their mothers - Nayera E. Hassan; Sahar A. El-Masry; Waheba Zarouk; Rokia A. El Banna; Rehab M. Mosaad; Muhammad Al-Tohamy; Abeer Ramadan Salamah (Genes and Diseases, 2018)
Obesity is complex heterogeneous disease controlled by genes, environmental factors, and their interaction. Genetic factors account for 40–90% of the body mass index variations. Body mass index (BMI) of children correlates more closely with maternal than paternal BMI. So, this studu was aimed to investigate the role of leptin receptor LEPR Gln223Arg, the uncoupling protein 2 (UCP2 G 866 A) and insulin receptor gene (INSR exon 17) polymorphisms in the pathogenesis of obesity. A cross-sectional study executed on 130 children and their obese mothers; classified into 2 groups according to their BMI. The 2 groups were evaluated regarding the anthropometry. Restriction fragment length analysis for LEPR Gln223Arg, UCP2 -866 G/A and INSR exon 17 polymorphisms were applied. It was reported that increased risk of obesity was found in LEPR AG + AA genotype and the A allele. Significant statistical difference was detected only in female children. Concerning UCP2, the AG followed by the GG genotype was the most frequent in all groups and the G allele was the mostly present in obese mothers and obese male children but with no statistical significance. There was difference in the INSR genotype and alleles between groups, but this difference was not statistically significant. This study concluded that the LEPR Gln223Arg, UCP2 G 866 A and INSR exon 17 polymorphisms are related to obesity in Egyptian population. Further researches on larger population are recommended to ascertain the implications of LEPR, UCP2 and INSR polymorphisms in obesity. Keywords: Egyptian, Gene polymorphism, Insulin receptor (INSR), Leptin receptor (LEPR), Obesity, Uncoupling protein 2 (UCP2), Phenotype